Good Corporate Governance as Oversight of Earnings Management Quality - Yanto, Desri; Fithri, Eka Jumarni; Masnila, Nelly; Amaliah, Neisya; Anjani, Rija; Rizki , Mutiara (LPPM Universitas Jambi, 2026)
This study examines the efficacy of Good Corporate Governance (GCG) as an oversight mechanism against earnings management, utilizing audit quality as a moderating variable. Employing a quantitative methodology, the research population comprises basic industry and chemical companies listed on the Indonesia Stock Exchange (IDX) spanning the 2022–2025 period. Through purposive sampling from an initial pool of 95 firms, a final sample of 76 companies was selected, yielding 304 firm-year observations. Empirical findings demonstrate that the proportion of independent commissioners, the presence of female commissioners on the board, and the board's financial and accounting expertise all exert a significant negative effect on earnings management. Furthermore, audit quality is proven to strengthen the mitigating effect of these three board characteristics on earnings management practices. The implications of this study suggest that fostering board independence, gender diversity, and specialized financial expertise, coupled with high-quality external audits, is critical for constraining opportunistic managerial behavior and safeguarding the integrity of financial reporting.